Analysis of Lecturers’ Work Performance Based on Pedagogy Competence and Work Motivation (International Journal of Scientific Research and Management (IJSRM), 2018)
Lecturers’ work performance is one of the most crucial factors in the attainment of success of the university’s vision. Thus, extra attempts need to be done in enhancing factors that influence the work performance. The objective of this research is to determine the effect of pedagogy competence and work motivation toward lecturers’ work performance. The research is conducted using the quantitave approach. Research samples selected as much as 172 permanent lecturers of Universitas Persatuan Guru Republik Indonesia (UPGRI) Palembang. Foundation research data are collected through test and questionnaire. Further, data collected are analyzed using t-test and path analysis. Based on the research, it is found that: (1) there is direct positive effect of the pedagogy competence toward work performance; (2) there is direct positive effect of the work motivation toward work performance;(3) there is direct positive effect of the pedagogy competence toward work motivation. The conclusion is that work motivation needs to be firstly improved than the pedagogy competence so as to level up the work performance of UPGRI Palembang lecturers. Keywords: Work performance, Pedagogy competence, Work motivation.